Overloaded and stressed: whole-cell considerations for bacterial synthetic biology. (October 2016) - Borkowski, Olivier; Ceroni, Francesca; Stan, Guy-Bart; Ellis, Tom
Highlights: Predictability and robustness are major challenges for synthetic biology. Engineering bacteria requires putting synthetic constructs into growing host cells. Synthetic constructs impact on the physiology and health of their host cells. The physiology of the host cell impacts on the performance of synthetic constructs. New tools to allow us to measure, reduce and predict host–construct interactions. Abstract : The predictability and robustness of engineered bacteria depend on the many interactions between synthetic constructs and their host cells. Expression from synthetic constructs is an unnatural load for the host that typically reduces growth, triggers stresses and leads to decrease in performance or failure of engineered cells. Work in systems and synthetic biology has now begun to address this through new tools, methods and strategies that characterise and exploit host–construct interactions in bacteria. Focusing on work in E. coli, we review here a selection of the recent developments in this area, highlighting the emerging issues and describing the new solutions that are now making the synthetic biology community consider the cell just as much as they consider the construct.